2012
DOI: 10.1103/physrevb.86.155210
|View full text |Cite
|
Sign up to set email alerts
|

Spin-current absorption by inhomogeneous spin-orbit coupling

Abstract: We investigate the spin-current absorption induced by an inhomogeneous spin-orbit coupling due to impurities in metals. We consider the system with spin currents driven by the electric field or the spin accumulation. The resulting diffusive spin currents, including the gradient of the spin-orbit coupling strength, indicate the spin-current absorption at the interface, which is exemplified with experimentally relevant setups.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…In this case the Fermi level intersects only the lower band and only the annulus lying between the two Fermi circles of radii k −1,−2 (E F ) is filled. This nontrivial topology of Fermi surfaces in the band valley has been highlighted in previous researches [1][2][3] . Substituting the electron density into Eq.…”
Section: The Chemical Potential At Low Temperaturesmentioning
confidence: 54%
See 1 more Smart Citation
“…In this case the Fermi level intersects only the lower band and only the annulus lying between the two Fermi circles of radii k −1,−2 (E F ) is filled. This nontrivial topology of Fermi surfaces in the band valley has been highlighted in previous researches [1][2][3] . Substituting the electron density into Eq.…”
Section: The Chemical Potential At Low Temperaturesmentioning
confidence: 54%
“…In addition, spin-related thermoelectric conversion in systems with strong Rashba SOC is gathering increasing attention, which is not only essential for exploring spintronics devices 16 but also important for developments of spin caloritronics 17 . For Rashba 2DES, based on the relaxation time approximation (RTA) 2,10,18 in the semiclassical Boltzmann equation (SBE) approach, it has been suggested recently that the dimensional reduction of the electronic structure from 2D to 1D can result in enhancements of the diffusive thermopower and thermoelectric figure of merit 10 ZT = (α/σ) 2 σT /κ. Here σ, α, κ and T denote the electrical conductivity, Peltier coefficient, thermal conductivity, absolute temperature, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…The RSOI has potential applications in developing spintronic devices as its strength is externally tunable 7 and therefore it is mostly studied. It is revealed that the RSOI can host a plethora of exotic phenomena such as dissipationless spin current 8,9 , spin Hall effect [10][11][12][13][14][15] , spin-orbit torque 15,16 and spin galvanic effect 15,17 .…”
Section: Introductionmentioning
confidence: 99%
“…At temperatures much smaller than the Debye temperature θ D , number of phonons participating in thermal transport will be very small and electronic thermal conductivity will dominate over the lattice counterparts. For instance, in B20 compounds like Fe 1−x Co x Si 52 θ D is around 350 K and in MnGe, CoGe 53 θ D is about (269-281) K. Therefore, in this work we consider the temperature around (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) K which is much smaller than θ D . Moreover, it is essential to have low temperature of the system so that thermal energy is always less than the spin splitting energy which is required to control spin of a charge carrier for spintronic device applications.…”
Section: Introductionmentioning
confidence: 99%
“…This regime possesses nontrivial topology of the constant energy surfaces (or Fermi surfaces) [16], which leads to some exciting theoretical predictions, e.g., the enhanced superconducting critical temperature [16], the non-Dyakonov-Perel spin relaxation behavior [17] and the significantly enhanced room-temperature thermoelectric figure of merit [18]. There have been a few theoretical studies [14,[17][18][19][20] on the transport properties when the Fermi energy is in or near the band valley regime. However, in Rashba systems formed in conventional narrow-gap semiconductor heterostructures [21], the Rashba spin splitting energy is so small that the band valley structure can not survive the weak disorder broadening and thermal smearing even at very low temperatures.…”
Section: Introductionmentioning
confidence: 99%